2010
DOI: 10.1016/j.neuron.2010.03.024
|View full text |Cite
|
Sign up to set email alerts
|

The Androgen Receptor Governs the Execution, but Not Programming, of Male Sexual and Territorial Behaviors

Abstract: SUMMARY Testosterone and estrogen are essential for male behaviors in vertebrates. How these two signaling pathways interact to control masculinization of the brain and behavior remains to be established. Circulating testosterone activates the androgen receptor (AR) and also serves as the source of estrogen in the brain. We have used a genetic strategy to delete AR specifically in the mouse nervous system. This approach permits us to determine the function of AR in sexually dimorphic behaviors in males while m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
198
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(214 citation statements)
references
References 86 publications
(121 reference statements)
16
198
0
Order By: Relevance
“…The transient increase of AR mRNA levels in the hypo may reflect the existence of similar regulation by testosterone in mice. It was reported that mutant male mice with a deletion of AR specifically in the central nervous system displayed a reduced masculinized repertoire of mating and territorial fighting and marking behaviors [8,22]. In these mutant males, a dramatic decrease in AR expression in the brain at PD1 was also observed, compared to control littermates.…”
Section: Discussionmentioning
confidence: 98%
“…The transient increase of AR mRNA levels in the hypo may reflect the existence of similar regulation by testosterone in mice. It was reported that mutant male mice with a deletion of AR specifically in the central nervous system displayed a reduced masculinized repertoire of mating and territorial fighting and marking behaviors [8,22]. In these mutant males, a dramatic decrease in AR expression in the brain at PD1 was also observed, compared to control littermates.…”
Section: Discussionmentioning
confidence: 98%
“…Recent work in California mice shows that males respond to social victories in the home territory by increasing androgen receptor (AR) expression in select areas of the mesolimbic system and that these changes in neural androgen sensitivity are positively associated with winning [17]. Although the persistence and functionality of this newly expressed AR are not yet clear, heightened androgen sensitivity throughout the mesolimbic system may help intensify the output and motivational elements of future aggression [41,42]. Given this, white-footed mice may naturally sustain levels of mesolimbic AR that are sufficient for postvictory T to enhance the reinforcing elements of aggression that compel mice to fight [43].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, male mice lacking ERa also fail to exhibit any sexual behavior. In contrast, animals with a brain-specific deletion of AR retain low levels of sexual behavior, but mount and intromit at a much lower frequency than controls [14]. These steroid hormone receptors are cognate nuclear receptors, which upon ligand binding translocate to the nucleus to regulate expression of target genes.…”
Section: Separable Genes Control Distinct Behavioral Parametersmentioning
confidence: 99%